Bimbingan Dasar-Dasar Ilmu Fiqh Kepada Murid-Murid Sekolah Rendah Islam Anakku Imtiyaz Bandar Bukit Raja Malaysia - Ar, Samsul; Jamil, Rahmat Jamil Arroziqi; Ach. Athoillah, Ach. Athoillah; Mustaqim, Mustaqim (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2024)
Since an early age, children need to be introduced to the basics of fiqh in order to understand and practice Islamic teachings in everyday life. It very important for children in Malaysia learning basic fiqh is as a basis for forming the basics of Islam from in early age. This community service activity is part of educating the lives of humanity in Malaysia. This report is a documentation of the activities of basic fiqh guidance using the JAKIM and JAIS curriculum teaching media in Malaysia, combined with various fiqh practice programs that can be applied directly in schools. Basic fiqh guidance for students of Sekolah Rendah Islam Anakku Imtiyaz Bandar Bukit Raja was carried out using the Participatory Action Research (PAR) approach. This approach basically focuses on the potential and assets that currently exist in the community, with the aim of developing and empowering these assets so that they can function optimally. Fiqh is included in Islamic religious knowledge that must be instilled from an early age, because fiqh is a science that discusses a Muslim's worship to his God. Guidance on the basics of fiqh science is one way to guide children in understanding the basics of fiqh science and practicing it consistently